An overview of the utilisation of microalgae biomass derived from nutrient recycling of wet market wastewater and slaughterhouse wastewater - A. Y., Maizatul; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel A.; Amir Hashim, M. K. (Springer International Publishing, 2017)
Microalgae have high nutritional values for aquatic organisms compared to ﬁsh meal, because microalgae cells are rich in proteins, lipids, and carbohydrates. However, the high cost for the commercial production of microalgae biomass using fresh water or artiﬁcial media limits its use as ﬁsh feed. Few studies have investigated the potential of wet market wastewater and slaughterhouse wastewater for the production of microalgae biomass. Hence, this study aims to highlight the potential of these types of wastewater as an alternative superior medium for microalgae biomass as they contain high levels of nutrients required for microalgae growth. This paper focuses on the beneﬁts of microalgae biomass produced during the phycore-mediation of wet market wastewater and slaughterhouse wastewater as ﬁsh feed. The extraction techniques for lipids and proteins as well as the studies conducted on the use of microalgae biomass as ﬁsh feed were reviewed. The results showed that microalgae biomass can be used as ﬁsh feed due to feed utilisation efﬁciency, physiological activity, increased resistance for several diseases, improved stress response, and improved protein retention.